Impact of economic growth on the changes in forest resources in Inner Mongolia of China - Wu, Xiaoyu; Liu, Guiyan; Bao, Qingfeng (Frontiers in Environmental Science, 2023)
Balancing the relationship between forest resources and economic growth is crucial for achieving sustainable development in China. Inner Mongolia, with its unique geographical environment and relatively underdeveloped economy, exhibits distinctive patterns in its forest resources development and changes. This study investigates the impact of economic growth on forest resources in Inner Mongolia using time-series data from 1980 to 2018 and the cubic curve regression model based on the Environmental Kuznets Curve (EKC) hypothesis. The results reveal an inverted N-shaped EKC relationship, with the forest coverage rate undergoing a "decline-up-decline" evolution process, characterized by turning points 1984 and 2015, and the forest stock volume exhibiting a "decline-up" evolution process with a minimum turning point around 1999. Remarkably, the forest stock volume continues to increase at present and over a foreseeable future. Furthermore, the study finds that population density has a negligible effect on the reduction of forest coverage rate in Inner Mongolia.